Drgania Swobodne Niejednorodnej Błony Pierścieniowej - Vodička, V. (Engineering Transactions, 1962)
An annular membrane go < g < gn is assumed to be composed of n homogeneous parts gk-1 < g < gn, 1 < k < n with surface densities ox, 1 < k < n. The problem is to determine the natural vibration if the initial state is determined by given functions f (g), g (g) and the membrane is subject to a uniform tension S.The solution is obtained by means of the classical method of characteristic functions, which gives an interesting view of these problems and has formal advantages. The general results are applied to the special case of a homogeneous membrane.